Popular democracy in Japan : how gender and community are changing modern electoral politics - Martin, Sherry L., 1971- (Cornell University Press, 2011)
Popular Democracy in Japan examines a puzzle in Japanese politics: Why do Japanese women turn out to vote at rates higher than men? On the basis of in-depth fieldwork in various parts of the country, Sherry L. Martin argues that the exclusion of women from a full range of opportunities in public life provokes many of them to seek alternative outlets for self-expression. They have options that include a wide variety of study, hobby, and lifelong learning groups-a feature of Japanese civic life that the Ministry of Education encourages. Women who participate in these alternative spaces for learning tend, Martin finds, to examine the political conditions that have pushed them there. Her research suggests that study group participation increases women's confidence in using various types of political participation (including voting) to pressure political elites for a more inclusive form of democracy. Considerable overlap between the narratives that emerge from women's groups and a survey of national public opinion identifies these groups as crucial sites for crafting and circulating public discourses about politics. Martin shows how the interplay between public opinion and institutional change has given rise to bottom-up changes in electoral politics that culminated in the 2009 Democratic Party of Japan victory in the House of Representatives election.